ANALISIS PENYERAPAN TENAGA KERJA PADA SEKTOR EKSPEDISI DI KABUPATEN ACEH BARAT - Pangestu, Denanda (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2025)
This study aims to analyze the influence of capital, wage levels, and technology on labor absorption in the expedition sector in West Aceh Regency. The expedition sector plays an important role in providing employment, especially in facing the challenges of increasing unemployment due to population growth. With the development of shipping activities, the need for labor also changes, depending on the adequacy of capital, the amount of wages, and the use of technology. This study uses a quantitative approach with a causal associative method. The research sample covers the entire population, namely 26 expedition company units in West Aceh Regency which were taken using the total sampling technique. Primary data were obtained by distributing questionnaires to respondents in each company. The data analysis technique used is multiple linear regression, with classical assumption tests such as normality, multicollinearity, heteroscedasticity, and autocorrelation tests to ensure the validity of the model. The results of the study indicate that partially, the capital and technology variables have a positive and significant effect on labor absorption, while the wage level does not have a significant effect. However, simultaneously, the three variables capital, wages, and technology have a positive and significant effect on labor absorption in the expedition sector of West Aceh Regency. These findings suggest that increasing capital and adopting appropriate technology can expand employment opportunities, while wage policies need to be considered with a more comprehensive approach to encourage employment absorption.